A design-based research perspective for multiple immersive digital conversations in academic research writing literacies - Ngodwana, Khanyisile (School of Education, 2025)
In the South African higher education context, academic writing support at the postgraduate level presents significant challenges for institutions. The conventional dyadic models of writing support, typically offered by writing centres, are increasingly viewed as inadequate in addressing the multifaceted nature of academic writing and literacy challenges. This study advocates for a shift towards a more inclusive and holistic approach, promoting trialogic and multi-lateral conversations within writing centres to address these challenges. The study's methodology is deeply rooted in literature and adopts Reeves' (2006) four-phase model to guide the Design-Based Research (DBR) approach. Through two iterative intervention cycles, the study integrates efforts from writing centres and subject lecturers to facilitate immersive conversations aimed at academic research literacy development. The third phase of DBR intensively focuses on testing and refining the interventions to address directly identified obstacles. The effectiveness of these interventions is measured through qualitative data collection methods, including surveys, interviews, observations, and document analysis. The study aims to answer the question: What are the design principles for facilitating multiple immersive digital conversations in academic research writing literacies? To answer this question, the study creates a dynamic and interactive environment where students can engage in meaningful dialogues and collaborative activities by integrating digital tools like Google Drive into the learning process. The study develops an integrated theoretical framework for multiple immersive digital conversations for academic research writing that interlinks linguistic, cognitive, and social elements. The study's participants include Bachelor Honours students and Advanced Diploma students, writing centre practitioners, and academic supervisors at a university in South Africa. The theoretical contribution of the study is a model of refined design principles for developing a robust intervention for multiple immersive digital conversations in academic research writing literacies. These principles advocate for pedagogies that respect and incorporate students' identities, aligning with adaptive and culturally inclusive teaching practices. In the realm of academic writing instruction, these principles have the potential to improve support systems significantly, enhancing students' academic achievements and advancing their research literacy skills.